PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS PETERNAKAN DAN PERIKANAN KABUPATEN LAMONGAN - Mudzakkir, Ahmad (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2016)
The notion of performance is the result of the quality and quantity of work achieved by someone employee in performing their duties in accordance with the responsibilities given to him. Respondents were employees of Department of Animal Husbandry and Fisheries Lamongan the sample in this study were 63 respondents are employees of the Department of Animal Husbandry and Fisheries Lamongan ever take part in education and training. From the results of the questionnaire respondents behavioral variables, namely the number of 34.58%, ie knowledge variable number of 28.86%, which is a variable 22.79% skill, attitude variables ie number of 12.04%. Results F arithmetic amounted to 6.681> f Table 2.55 with probability 0,0029. From the results of the partial t test all link variables significantly affect the performance of the Civil Service Department of Animal Husbandry and Fisheries Lamongan. Variable link consists of variable Knowledge, Skills, Attitudes and Behavior jointly have a significant influence on the performance of the Civil Service Department of Animal Husbandry and Fisheries Lamongan. This situation ditunukkan of the correlation coefficient R = 0.9807 (98.07%) is close to 1 (100%). This shows that there is a very strong positive relationship between the independent variables (X1, X2, X3, and X4) simultaneously to the dependent variable (Y). While the coefficient of determination (R2) = 0.9618 (96.18%). This means that the independent variables are jointly able to contribute to the independent variables of 96.18%.